Sodobna slovaška proza in ritual z vidika uporabe pripovednih in jezikovnih sredstev (na primeru novele Kataríne Kucbelove Čepiec) - Kmecová, Svetlana (Jezik in slovstvo, 2025)
The article analyses Katarína Kucbelová’s novella The Bonnet (Čepiec, 2019), which represents one of the tendencies in contemporary Slovak fiction, highlighting the question of identity and the relationship to tradition in a regionally, ethnically and confessionally diverse environment. The basis of our linguistic and literary analysis is ritual, which has long been at the centre of attention in ethnological, anthropological, cultural and also linguistic research. We are interested in how it is manifested in the text in terms of literary procedures and the choice of linguistic devices used. The literary part of the analysis deals with the use of narrative strategies related to ritual (thematically, genre-wise, structurally). The linguistic part focuses on the linguistic means used by the author to achieve the effects of rituality, mainly through the choice of lexis, symbols, metaphors and phraseology, and examines the texts under study mainly from an ethno-linguistic perspective.
Keywords: contemporary Slovak prose; ethnolinguistics; etnolingvistika; jezikovna analiza; Kucbelová, Katarína; linguistic analysis; narrative strategies; pripovedne strategije; ritual; Slovak literature; slovaška književnost; sodobna slovaška proza